Ibn Khaldun's Thoughts on Islamic Educational Governance: Uniting Science and Ethics in Leadership Practice - Mokhamad Yaurizqika Hadi; Dhea Queenta Auliya; Su’ud Intan; Masaayu Huril Ain Kuni Afifah (Cyber Media Indonesia, 2026)
This study explores Ibn Khaldun's ideas on Islamic educational management by emphasizing the integration of knowledge and morality in educational leadership practices. As an influential Muslim intellectual in the fields of sociology, education, and the philosophy of history, Ibn Khaldun viewed knowledge as the main pillar of civilizational progress, while morality functions as the ethical compass guiding its application. This research employs a qualitative approach through a literature review, focusing primarily on Ibn Khaldun’s monumental work, the Muqaddimah, as well as other relevant scholarly sources. The findings reveal that Ibn Khaldun conceptualized education as a holistic process aimed at developing individuals who are not only intellectually competent but also morally mature. In the context of educational leadership, he highlighted the importance of exemplary leadership, justice, ethical responsibility, and the cultivation of virtuous character. The practical implications of these findings suggest that contemporary Islamic educational institutions can adopt Ibn Khaldun’s framework by strengthening value-based leadership, integrating moral education into institutional governance, and fostering a learning environment that balances intellectual excellence with ethical integrity. Consequently, the integration of knowledge and morality, as formulated by Ibn Khaldun, provides a relevant and strategic foundation for developing a holistic and sustainable model of Islamic educational management in the modern era. Abstrak Penelitian ini mengkaji pemikiran Ibn Khaldun tentang manajemen pendidikan Islam dengan menekankan integrasi antara ilmu pengetahuan dan moralitas dalam praktik kepemimpinan pendidikan. Sebagai seorang intelektual Muslim yang berpengaruh dalam bidang sosiologi, pendidikan, dan filsafat sejarah, Ibn Khaldun memandang ilmu pengetahuan sebagai pilar utama kemajuan peradaban, sementara moralitas berfungsi sebagai kompas etis dalam penerapannya. Penelitian ini menggunakan pendekatan kualitatif melalui studi pustaka dengan menelaah karya monumental Ibn Khaldun, yaitu Muqaddimah, serta berbagai sumber ilmiah pendukung lainnya. Hasil penelitian menunjukkan bahwa Ibn Khaldun memandang pendidikan sebagai proses holistik yang bertujuan untuk membentuk individu yang tidak hanya unggul secara intelektual, tetapi juga matang secara moral. Dalam konteks kepemimpinan pendidikan, ia menekankan pentingnya keteladanan pemimpin, keadilan, tanggung jawab etis, serta pembinaan karakter yang luhur. Implikasi praktis dari penelitian ini menunjukkan bahwa lembaga pendidikan Islam kontemporer dapat mengadopsi kerangka pemikiran Ibn Khaldun dengan memperkuat kepemimpinan berbasis nilai, mengintegrasikan pendidikan moral dalam tata kelola lembaga, serta menciptakan lingkungan pembelajaran yang menyeimbangkan keunggulan intelektual dengan integritas moral. Dengan demikian, integrasi antara ilmu pengetahuan dan moralitas sebagaimana dirumuskan oleh Ibn Khaldun menjadi landasan penting dalam pengembangan model manajemen pendidikan Islam yang holistik dan berkelanjutan di era modern.